FRI0243 SARCOPENIA IS ASSOCIATED WITH MALNUTRITION IN PATIENTS WITH SYSTEMIC SCLEROSIS. (2nd June 2020) - Hax, V.; Cavalheiro Do Espírito Santo, R.; Pena, E.; Rodrigues, L.; Pedo, R. T.; Miranda de Souza Silva, J.; Pamplona Bueno de Andrade, N.; Gasparin, A. A.; Xavier, R.; Mendonça Da Silva Chakr, R.
Abstract : Background: Sarcopenia is one of the major health problems in older patients and is defined as a progressive decrease in muscle mass and function 1 . Sarcopenia has only rarely been studied in systemic sclerosis (SSc) and its impact in clinical characteristics of SSc is poorly investigated. Objectives: To evaluate the associations between sarcopenia and clinical features in SSc patients. Methods: Cross-sectional study, including 82 patients who met the ACR/EULAR 2013 classification criteria for SSc. Dual-energy X-ray absorptiometry, handgrip strength, and short physical performance battery were used to assess sarcopenia according the European Working Group on Sarcopenia in Older People's (EWGSOP) diagnostic criteria updated in 2019 1 . Malnutrition was evaluated according to the European Society of Clinical Nutrition and Metabolism (ESPEN) 2, using the Malnutrition Universal Screening Tool (MUST) to screen risk for malnutrition. Results: The mean age was 60.4 years and 91.5% were women (table 1 ). Sarcopenia was identified in 15 (18.3%) SSc patients. Malnutrition was diagnosed in 12 (14.6%) and was more common in patients with sarcopenia ( P= 0.038). Also, there were significant differences between patients with and without sarcopenia regarding Body Mass Index ( P =0.001), Fat Free Mass Index ( P <0.001), knee extension strength ( P =0.049), and Timed Up and Go test ( P =0.041). There were no differences regarding age, disease duration, Rodnan skin score (mRSS), FVC and DLCO. Conclusion: Sarcopenia is relatively common and is associated with malnutrition in patients with SSc. In our population, sarcopenia was not associated with other features related to a more severe disease. The role of sarcopenia in the prognosis of SSc needs to be better understood in longitudinal studies. References: [1]Cruz-Jentoft AJ, Bahat G, Bauer J, et al. Sarcopenia: Revised European consensus on definition and diagnosis. Age Ageing. 2019;48(1):16-31. [2]Cederholm T, Bosaeus I, Barazzoni R, et al. Diagnostic criteria for malnutrition - An ESPEN Consensus Statement. Clin Nutr. 2015;34(3):335-40 Disclosure of Interests: Vanessa Hax: None declared, Rafaela Cavalheiro do Espírito Santo: None declared, Emerson Pena: None declared, Luísa Rodrigues: None declared, Renata Ternus Pedo: None declared, Jordana Miranda de Souza Silva: None declared, Nicole Pamplona Bueno de Andrade: None declared, Andrese Aline Gasparin: None declared, Ricardo Xavier Consultant of: AbbVie, Pfizer, Novartis, Janssen, Eli Lilly, Roche, Rafael Mendonça da Silva Chakr: None declared